The Rusunawa's Strategy For Increasing Students' Enthusiasm For Learning In Taking Routine Studies At Rusunawa , Muhammadiyah University, North Sumatra - Ayustia, Husni; Anisa, Vina; Alhafiz, Jehanda; Girsang, Hamidah Nurul Badri (Berpusi Publishing, 2023)
The Rusunawa management strategy in participating in routine studies at the Muhammadiyah University of North Sumatra is very necessary because it is to find out the results obtained from the program implemented by the Muhammadiyah University of North Sumatra so that student character improves as evidenced by students in the dormitory knowing the Rusunawa management system in improving student character education in Muhammadiyah University of North Sumatra. To find out the rusunawa program in knowing the obstacles to rusunawa management in improving the character education of students at the Muhammadiyah University of North Sumatra. This research uses descriptive methods and is analyzed using a qualitative approach. The subjects in this research were Muhammadiyah University students North Sumatra . Based on the research results, it shows that (1) The Rusunawa management system in improving the Character Education of Muhammadiyah University of North Sumatra students has 2 approach systems, namely the Traditional system and the University system. (2) The Rusunawa program to improve student character at the Muhammadiyah University of North Sumatra, namely the Character, Mentoring , Social education program.